Islam dan Modernitas: Pandangan Muslim terhadap Perkembangan Sosial, Politik dan Sains - Maula, Bani Syarif (FIKRAH, 2017)
Islam is always highlighted by the world, among others in relation to the values of modernity, since some Muslims indeed reject the values contained in the modernity. This paper explains the Muslim response to the values of modernity in the social and political field, as well as the field of science. The social and political field explains issues of nationalism, democratization, and human rights. While in the field of science will highlight the issue of Muslim view of the theory of evolution. A theory that forms the basis for the development of modern science. The modernity that plagues the Islamic world, with all its positive-negative effects, becomes a challenge that Muslims must face today in contemporary times. Muslims are required to work extra hard to develop their potential to solve the problem. Tajdid and ijtihad are efforts by Muslims to preserve and preserve Islamic teachings to conform to modern values.